Managing Differences and Building Trust: Challenges to U.S. – China Relations - Nur Rachmat Yuliantoro (Global South Review, 2014)
The relations between two great nations, the United States and China, have attracted the attention of many. Different in several aspects, both countries face a number of challenges and problems in their relationship, ranging from misperception, mutual distrust, and the potential for conflict in the South China Sea as well as East China Sea. The leaders of both countries have difficult task to drive the bilateral relations positively for mutual benefit. This article demonstrates that while to some extent their differences are difficult to settle, they need to be put aside to build mutual trust as a basic ground for cooperation. Unfortunately, it seems that their relations in the future has still characterized, among others, by the absence of the will to understand each other.